Complex carbohydrate specificity of lectin from fruiting body of ganoderma lucidum. a surface plasmon resonance study - Thakur, Atul; Pal, Lakhan; Ahmad, Absar; Khan, Mohammad Islam (IUBMB Life, 2007)
The thermodynamics and kinetics of binding of glycans and glycoproteins to Ganoderma lucidum lectin was studied using surface plasmon resonance. The lectin showed highest affinity for asialo triantennary N glycan (Ka = 3.52 x 10(5)) among the glycans tested. There was a several fold increase in affinity for glycoproteins compared to their corresponding glycans and coincident increase in contribution from enthalpy (Delta H), suggesting the involvement of hydrogen bonding in the interaction as well as involvement of protein-protein interactions. Increased affinity also showed increase in unfavorable negative binding entropy (Delta S) which was compensated with higher enthalpy. The glycoproteins showed faster association rates (k(1)) and the activation energy (E-1(double dagger)) in the association process was much lower for the glycoproteins than glycans, resulting in their faster associations. These observations elaborate the role of protein matrix in lectin-glycoconjugate interaction.
Keywords: ganoderma lucidum; glycans; Lectin; SPR

Purification and characterization of a lectin from endophytic fungus fusarium solani having complex sugar specificity - Khan, Feroz; Ahmad, Absar; Khan, Mohammad Islam (Archives of Biochemistry and Biophysics, 2007)
A lectin from the mycelial extract of an endophytic strain of Fusarium solani was purified. Its hemagglutinating activity was inhibited by glycoproteins possessing N-linked as well as O-linked glycans. The thermodynamics and kinetics of binding of glycans and glycoproteins to F. solani lectin Was Studied using SUH ace plasmon resonance. The lectin showed high affinity for asialofetuin, asia-lofibrinogen, asialofibrinogen, and thyroglobulin: and comparatively low affinity for mucin, fetuin, fibrinogen, and holotransferrin. Glycoproteins showed glycans with significant contribution from enthalpy and positive entropy, suggesting several fold higher affinity than their corresponding g the involvement of non-polar protein-protein interaction. Moreover, the higher affinity of the glycoproteins was due to their faster association rates and low activation energy. (c) 2006 Elsevier Inc. All rights reserved.
Keywords: endophytic fungus; Fusarium solani; Lectin; Purification; SPR; Thermodynamic properties

Enhanced electrochromic coloration in Ag nanoparticle decorated WO3 thin films - Kharade, Rohini R.; Mali, Sawanta S.; Patil, Satish P.; Patil, Kashinath R.; Gang, Myong G.; Patil, Pramod S.; Kim, Jin H.; Bhosale, Popatrao N. (Electrochimica Acta, 2013)
WO3/Ag composite thin films were prepared by microwave assisted sol-gel synthesis (MW-SGS) of WO3 followed by vacuum evaporation of Ag nanoparticles and their enhanced electrochromic coloration was investigated. The composition and morphology of WO3 thin films with different thickness of Ag layer obtained by vacuum evaporation were investigated. Distinct plasmon absorption bands of Ag nanoparticle thin films were obtained. The optical band gap energy of WO3/Ag films decreased with increasing the Ag layer thickness. The surface of these films has been examined using X-ray photoelectron spectroscopy (XPS) to gain information about the chemical states of species present at surfaces. Experimental results indicated that the conductivity of the films increased after surface modification by Ag layer. To investigate the origin of enhanced electrochromic absorption in optical properties, working electrode consisting of WO3/Ag thin film was used and observed the optical properties during electrochemical reaction. It was found that composite electrode shows enhancement in electrochromic properties in terms of optical modulation (Delta OD) and coloration efficiency (eta). (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Ag2WO4; CIE coordinates; Electrochromism; SPR; WO3/Ag composite thin films